Horizontal gene transfer - Syvanen, Michael; Kado, Clarence I. (Academic Press, 2002)
The second edition of Horizontal Gene Transfer has been organized to provide a concise and up-to-date coverage of the most important discoveries in this fascinating field. Written by the most prominent gene transfer and genome analytical scientists, this book details experimental evidence for the phenomenon of horizontal gene transfer and discusses further evidence provided by the recent completion of genomic sequences from Archea, Bacteria, and Eucarya members. The relevance of horizontal gene transfer to plant and metazoan taxonomy, GM foods, antibiotic resistance, paleontology, and phylogenetic reconstruction is also explored. Horizontal Gene Transfer is essential for microbiologists, geneticists, biochemists, evolutionary biologists, infectious disease specialists, paleontologists, ecologists, and researchers working in plant/animal systematics and agriculture with an interest in gene transfer. This includes scientific researchers from government and industry concerned with the release of genetically modified organisms. Up-to-the-minute reviews, maps, conclusions, urls to relevant websites and colour figures. Unique chapters, for example one written by paleontologists presents data for horizontal gene transfer from fingerprints form the fossil record.